The universal encyclopedia of machines (London, 1972)
How things work supplies readily-understood answers to all the questions that perplex the layman and puzzle the inquisitive child in the age of the machine. It explains everything fromt he simplest household gadget to the most complex industrial process: the theory and practice of modern machines and methods from the ball-point pen to the jet engine, from the polaroid camera to radar.
Keywords: Công nghệ,Technology